Phenolic fingerprint of Macedonian propolis - Petreska Stanoeva, Jasmina; Stojchevski, Cvetan; Bankova, Vassya; Stefova, Marina (Society of Chemists and Technologists of Macedonia, 2024)
Propolis is a chemically complex resinous material collected by honeybees (Apis mellifera) from tree buds and resins, comprising plant exudates, secreted substances from bee metabolism, pollen and waxes. Its chemical composition depends strongly on the plant sources available around the beehive, which have a direct impact оn the quality and bioactivity of the propolis. In this study, the composition of phenolic compounds in 13 Macedonian propolis extracts was investigated by HPLC-DAD-ESI-MS/MS. Overall, the UV spectra, the MS and MS/MS data allowed the identification of 36 compounds. The major constituents of propolis were phenolic acids (caffeic and coumaric) and their esters (methyl, (iso)prenyl, benzyl, phenylethyl, cinnamyl), flavonols (quercetin, kaemferol), flavones (chrysin, apigenin, acacetin), flavanonols (pinobanksin) flavanones (pinocembrin naringenin, hesperetin, pinostrobin) and their methylated/esterified derivatives. The results reveal that Macedonian propolis contains a diversity of phenolic compounds confirming that it is a poplar type of propolis with higher phenolic content (ranging from 43.75–637.94 mg/g) than reported in previous studies in the region and beyond in Europe (< 80 mg/g). This suggests the potential significance of Macedonian propolis as a valuable source of bioactive compounds with health benefits as well as for unlocking its economic potential for industry and beekeepers.